2016
DOI: 10.1007/s00414-016-1413-5
|View full text |Cite
|
Sign up to set email alerts
|

Disregarding population specificity: its influence on the sex assessment methods from the tibia

Abstract: Forensic anthropology has developed classification techniques for sex estimation of unknown skeletal remains, for example population-specific discriminant function analyses. These methods were designed for populations that lived mostly in the late nineteenth and twentieth centuries. Their level of reliability or misclassification is important for practical use in today's forensic practice; it is, however, unknown. We addressed the question of what the likelihood of errors would be if population specificity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 66 publications
3
14
0
Order By: Relevance
“…Amongst the basic biological features sex is the most studied with several methods marking high accuracies [1][2][3]. Scholars agree that most osteometric methods are population specific [4][5][6] with the exception of the pelvis [1,7]. Female pelvis is constructed to facilitate both bipedalism and parturition, thus the shape is notably different compared to the male pelvis.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the basic biological features sex is the most studied with several methods marking high accuracies [1][2][3]. Scholars agree that most osteometric methods are population specific [4][5][6] with the exception of the pelvis [1,7]. Female pelvis is constructed to facilitate both bipedalism and parturition, thus the shape is notably different compared to the male pelvis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, new research supports that several postcranial elements are actually better indicators of sex compared to the cranium [2]. In this vein, many population-specific studies have investigated the utility of the tibia as an indicator of sex and the accuracy of sex estimation when using the tibia as assessed by several morphometric parameters is over 84% [6][7][8][9][10][11][12][13][14][15][16][17] According to the religion of Islam, when a person dies, the first stage of the afterlife starts in the grave. Therefore, the use of dead bodies for scientific study purposes other than legal obligations is often impossible.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to produce population specific formulae for several different skeletal elements, including the tibia. Indeed, osteometric studies for sex estimation from the tibia have been conducted for several populations such as Northern Americans [11,12], medieval and modern Croatians [13,14] Portuguese [15], Southern Europeans [4], Czech [16] and Greek-Cypriots [17]. The high classification results (up to 95%) achieved in the abovementioned studies clearly makes the tibia a very successful sex indicator.…”
Section: Introductionmentioning
confidence: 99%
“…It was recommended the application of both methods due to low average accuracy obtained from the metric approach. Low classification accuracy was also noted in another study [38] European and North Americans were applied to a Czech sample. This study reported high misclassification of females and up to 100% sex bias.…”
Section: Discussionmentioning
confidence: 80%